TWO STAY TWO STRAY STRATEGY: A COOPERATIVE LEARNING MODEL TO IMPROVE STUDENTS’ SPEAKING SKILLS - Rekha Asmara (Language and Education Journal, 2018)
Speaking skill is the skill that is considered very important and cannot be separated from everyday life. If the interaction between a language speaker and the listener is not well established, the communication process cannot run smoothly. In the context of learning English in high school / vocational school, there are still many students who cannot convey their ideas or thoughts verbally especially when they are asked to speak about narrative text. Anxiety, shame, and fear of being laughed at are the causes that often arise when they will carry out speaking activities in front of the class. In addition, teacher-centered learning strategies are still often used by teachers so students are not fully involved in the learning process in the classroom. Of course, the impact is that students' skills in speaking narratives, in particular, become less honed. Students only get a little time to practice their speaking skills. So, here, Two Stay Two Stray strategy was believed to meet the students’ needs for improving their speaking skills in narrative texts